From: Keesings wereldgebeuren in beeld, no. 797. High commissioner for Palestine, Wauchope (centre) visiting the new harbour of Tel-Aviv. Second row, second from right the mayor of Tel-Aviv, Dizengoff
From: Keesings wereldgebeuren in beeld, no. 797. High commissioner for Palestine, Wauchope (centre) visiting the new harbour of Tel-Aviv. Second row, second from right the mayor of Tel-Aviv, Dizengoff.